USING POSTERS AS LEARNING MEDIA FOR FOREIGN LANGUAGE LEARNERS - Lina Septianasari; Erlinda Novita Sari (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2018)
This study aims to investigate the use of posters by young learners to learn English as foreign language. In line with the aim, this study administered descriptive qualitative research method to investigate the phenomenon. The participants in this research were teachers and students at a senior high school in Bogor, Indonesia. To collect the data, the authors used semi-structured interviews and documentation. The result of this research showed that posters could be used as an alternative medium during the learning process in the middle of remote teaching to maximize students’ learning motivation. Posters can be an alternative to be used as learning media to stimulate students’ speaking skill and vocabulary